UMP students begin returning home to cast votes - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
PAYA BESAR, 16 November 2022 - The excitement of the election began to be felt when some students returned to their hometowns to fulfill their responsibilities to the country and the vast majority are new voters who would vote in the 15th General Election (GE15) for the first time.